Diagnosis of Feline Panleukopenia Based on Clinical Signs and Polymerase Chain Reaction in Various Ages of Cats - Ramadhani, Mungky Ema; Indarjulianto, Soedarmanto; Yanuartono, Yanuartono; Raharjo, Slamet; Purnamaningsih, Hary; Widyarini, Sitarina; Milla, Yunita Apriana (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Feline panleukopenia (FPL) is a viral infectious disease caused by the feline panleukopenia virus (FPV) that affects cats of all ages. Clinical symptoms that appear in each individual cat vary greatly, depending on age, immune status, and the presence or absence of secondary infection. The aim of this research was to diagnose the FPL based on clinical signs and polymerase chain reaction (PCR) in cat with various ages. This study used 15 cats that showed one of clinical symptoms including lethargy, anorexia, fever, diarrhea, and vomiting. All cats were examined physically and by PCR of blood, then analyzed descriptively. The results showed that 10/15 (66.7%) cats were <7 months, 4/15 (26.7%) were 7-12 months, and 1/15 (6.6%) was >1 year old. Identification by PCR showed that 100% of the samples positive, so that all of cats diagnosed FPL. Clinical signs that commonly appeared in this study included anorexia (80%), fever (80%), vomiting (73.3%), lethargy (66.7%), and diarrhea (40%). Young cats <7 months commonly showed anorexia, fever, vomiting, and lethargy, cats aged 7-12 months commonly showed anorexia, fever, vomiting, and diarrhea, cat aged >12 months experienced anorexia and vomiting. Concluded that the predominant clinical symptoms of FPL in young cats were anorexia, fever, vomiting and lethargy, whereas in adult cats anorexia, fever, vomiting, and diarrhea. Clinical symptoms can be used for initial screening of FPL, but the causative diagnosis needs to be determined by polymerase chain reaction.